INCREASING LECTURER PROFESSIONALISM THROUGH INTERNATIONAL PUBLICATION IN PTS SE GROBOGAN DISTRICT - Widodo, Joko; Oktarina, Nina; Pramusinto, Hengky; Wati, Rizqi Mustika (Indonesian Journal of Devotion and Empowerment, 2019)
Community service activities carried out by the Community Service Team at PTS in Grobogan district aim to provide knowledge and skills regarding the preparation of scientific articles for international publications for PTS lecturers. The direct benefit of this community service activity is as additional knowledge, abilities and experience to PTS lecturers in Grobogan district in preparing articles for international publications. The expected benefit of derivatives is to increase the ability of lecturers in preparing scientific articles for international publications that will be able to improve the quality and quantity of international publications for PTS lecturers in Grobogan district and in the end will be able to increase the professionalism of lecturers. Community service activities are carried out in the form of training by providing material and practice in preparing scientific articles for international publications . The target audience of community service activities are lecturers PTS in Grobogan many as 20 people. The method of activities used in community service is the method of lecture, question and answer, discussion and practice. Evaluation of activities used in community service is the aspect of knowledge and skills. Kegiatan pengabdian kepada masyarakat yang dilaksanakan oleh Tim Pengabdian Kepada Masyarakat pada PTS di kabupaten Grobogan bertujuan untuk memberikan pengetahuan dan keterampilan mengenai penyusunan artikel ilmiah untuk publikasi internasional bagi dosen PTS. Manfaat langsung dari kegiatan pengabdian kepada masyarakat ini ialah sebagai tambahan pengetahuan, kemampuan dan pengalaman kepada dosen PTS di kabupaten Grobogan dalam penyusunan artikel untuk publikasi internasional. Manfaat turunan yang diharapkan adalah peningkatan kemampuan dosen dalam penyusunan artikel ilmiah untuk publikasi internasional akan dapat meningkatkan kualitas dan kuantitas publikasi internasional dosen PTS di kabupaten Grobogan dan pada akhirnya akan dapat menigkatkan profesionalisme dosen. Kegiatan pengabdian kepada masyarakat ini dilaksanakan dalam bentuk pelatihan dengan pemberian materi dan praktik penyusunan artikel ilmiah untuk publikasi internasional. Khalayak sasaran dari kegiatan pengabdian kepada masyarakat ini adalah dosen PTS di kabupaten Grobogan sebanyak 20 orang. Metode kegiatan yang digunakan dalam pengabdian kepada masyarakat ini adalah metode ceramah, tanya jawab, diskusi dan praktik. Evaluasi kegiatan yang digunakan dalam pengabdian masyarakat ini adalah aspek pengetahuan dan keterampilan.